Family history of PCOS, obesity, low fiber diet, and low physical activity increase the risk of PCOS - Alfaina Wahyuni; Supriyatiningsih; Wiwik Kusumawati; Kamila Sedah Kirana; Cynthia Dwi Mayayustika (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Polycystic ovarian syndrome (PCOS) is a common endocrine disorder and leading cause of prolonged anovulation. PCOS has been linked to a variety of long-term health problems, including: heart disease; metabolic syndrome; and diabetes. It is interesting to know the risk factors for PCOS in local settings.Objective: The aim of this research is to identify PCOS risk factors in our own settings (Asri Medical Center in Yogyakarta), so that we could identify the specific preparation to avoid having disorders personalized in localcharacteristics.Methods: This is a descriptive-analytic cross-sectional study. The research was carried out at Asri Medical Center in Yogyakarta, Indonesia, with a total sample size of 92 people who met the inclusion and exclusion criteria. They were divided into two groups: non-PCOS and PCOS. Data were retrieved using the questionnaire. The variables evaluated were nutritional status, physical activity, carbohydrate diet, fiber diet, family history of diabetes, family history of PCOS, and age of menarche. The data was analyzed usingthe Chi-square test.Results: Family history of PCOS, obesity, low physical activity and a lowfiber diet proved to differ significantly between the two groups (p<0.05).Conclusion: Family history of PCOS, obesity, low physical activity, low fiber diet had a substantial impact on the occurrence of PCOS.